Cigarette Smoking and Risk of Early Natural Menopause. Issue 4 (10th August 2017) - Whitcomb, Brian W; Purdue-Smithe, Alexandra C; Szegda, Kathleen L; Boutot, Maegan E; Hankinson, Susan E; Manson, JoAnn E; Rosner, Bernard; Willett, Walter C; Eliassen, A Heather; Bertone-Johnson, Elizabeth R
Abstract: Menopause before 45 years of age affects roughly 5%–10% of women and is associated with a higher risk of adverse health conditions. Although smoking may increase the risk of early menopause, evidence is inconsistent, and data regarding smoking amount, duration, cessation, associated risks, and patterns over time are scant. We analyzed data of 116, 429 nurses from the Nurses' Health Study II from 1989 through 2011 and used Cox proportional hazards models to estimate hazard ratios adjusted for confounders. Compared with never-smokers, current smokers (hazard ratio (HR) = 1.90, 95% confidence interval (CI): 1.71, 2.11) and former smokers (HR = 1.10, 95% CI: 1.00, 1.21) showed an increased risk of early menopause. Increased risks were observed among women who reported current smoking for 11–15 pack-years (HR = 1.72, 95% CI: 1.36, 2.18), 16–20 pack-years (HR = 1.72, 95% CI: 1.38, 2.14), and more than 20 pack-years (HR = 2.42, 95% CI: 2.11, 2.77). Elevated risk was observed in former smokers who reported 11–15 pack-years (HR = 1.29, 95% CI: 1.07, 1.55), 16–20 pack-years (HR = 1.42, 95% CI: 1.13, 1.79), or more than 20 pack-years (HR = 1.54, 95% CI: 1.23, 1.93). Women who smoked 10 or fewer cigarettes/day but quit by age 25 had comparable risk to never-smokers (HR = 1.03, 95% CI: 0.91, 1.17). A dose-response relationship between smoking and early natural menopause risk, as well as reduced risk among quitters, may provide insights into the mechanisms of cigarette smoking in reproductive health.